Religiosity, Attitude, and the Demand for Socially Responsible Products - Graafland, Johan J. (Journal of business ethics, 2017)
In this paper, we examine the relationship between various Christian denominations and attitude and behavior regarding consumption of socially responsible (SR) products. Literature on the relationship between religiosity and pro-social behavior has shown that religiosity strengthens positive attitudes towards pro-social behavior, but does not affect social behavior itself. This seems to contradict the theory of planned behavior that predicts that attitude fosters behavior. One would therefore expect that if religiosity encourages attitude towards SR products, it would also increase the demand for them. We test this hypothesis for four affiliations (non-religious, Catholic, Orthodox Protestant, and Other Protestant) on a sample of 997 Dutch consumers, using structural equation modeling. We find that Christian religiosity, indeed, increases positive attitude towards SR products, except for the Orthodox Protestant affiliation. In accordance with the theory of planned behavior, attitude is found to increase the demand for SR products. We find no evidence of hypocrisy (in the sense that religiosity increases pro-social attitude without affecting behavior in the case of SR products) for any of the Christian denominations.